1988
DOI: 10.1515/hfsg.1988.42.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Organosolv Delignification in Batch- and Flow-Through Reactors

Abstract: The kinetics of Organosolv delignification of black cottonwood in aqueous methanol was studied in the temperature ränge 130-210°C using 0.00 to 0.05 M sulfuric acid äs catalyst. The bulk delignification phase followed pseudo-first order kinetics with an activation energy of 19.2 kcal/mol (80.3 kJ/mol) suggesting the cleavage of benzyl ether linkages to be the rate determining reaction. At low catalyst concentrations (< 0.02 M sulfuric acid), the bulk rate constant of deashed cottonwood is nearly proportional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 4 publications
8
33
0
5
Order By: Relevance
“…In the hydrolysis of Quercus falcata wood by dilute sulphuric acid, however, the rate constant is only proportional to acid concentration if inorganic components of wood are removed with dilute HC1 prior to hydrolysis; otherwise, these components neutralize part of the HzSO 4 (Harris et al 1984). The fact that in our experiments the rate constants for neither the fast polysaccharide hydrolysis process nor the hydrolysis of lignin (V~zquez et al 1995) showed non-linear [HC1 ]-dependence indicative of partial neutralization may probably be attributed to the presence of acetic acid, which has been proposed as an alternative to HC1 for removal of the undesirable inorganic substances (Tirtowidjojo et al 1988). Fitting Arrhenius' equation to the values of kfc calculated by fitting Eq.…”
Section: Kinetics Of Polysaccharide Hydrolysismentioning
confidence: 54%
“…In the hydrolysis of Quercus falcata wood by dilute sulphuric acid, however, the rate constant is only proportional to acid concentration if inorganic components of wood are removed with dilute HC1 prior to hydrolysis; otherwise, these components neutralize part of the HzSO 4 (Harris et al 1984). The fact that in our experiments the rate constants for neither the fast polysaccharide hydrolysis process nor the hydrolysis of lignin (V~zquez et al 1995) showed non-linear [HC1 ]-dependence indicative of partial neutralization may probably be attributed to the presence of acetic acid, which has been proposed as an alternative to HC1 for removal of the undesirable inorganic substances (Tirtowidjojo et al 1988). Fitting Arrhenius' equation to the values of kfc calculated by fitting Eq.…”
Section: Kinetics Of Polysaccharide Hydrolysismentioning
confidence: 54%
“…Flow-through processes have been shown to improve the efficiency of different alkaline and organosolv delignification methods (Kadam et al, 2009;Park and Kim, 2012;Tae and Lee, 2005;Tirtowidjojo et al, 1988). Flow-through treatment is typically performed by percolation through material packed in a column.…”
Section: Introductionmentioning
confidence: 99%
“…Flow-through treatment is typically performed by percolation through material packed in a column. Compared to batch reactions, higher rate constants for lignin dissolution have been shown for percolation, leading to increased lignin dissolution and a lower degree of cellulose degradation (Tirtowidjojo et al, 1988). In hydrothermal pretreatments, flowthrough processes have also been shown to increase the dissolution of both hemicellulose (Liu and Wyman, 2005;Petersen et al, 2009) and lignin (Liu and Wyman, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations